CD70, a novel target of CAR T-cell therapy for gliomas. Issue 1 (23rd June 2017) - Jin, Linchun; Ge, Haitao; Long, Yu; Yang, Changlin; Chang, Yifan (Emily); Mu, Luyan; Sayour, Elias J; De Leon, Gabriel; Wang, Qiong J; Yang, James C; Kubilis, Paul S; Bao, Hongbo; et al.
Abstract: Background: Cancer immunotherapy represents a promising treatment approach for malignant gliomas but is hampered by the limited number of ubiquitously expressed tumor antigens and the profoundly immunosuppressive tumor microenvironment. We identified cluster of differentiation (CD)70 as a novel immunosuppressive ligand and glioma target. Methods: Normal tissues derived from 52 different organs and primary and recurrent low-grade gliomas (LGGs) and glioblastomas (GBMs) were thoroughly evaluated for CD70 gene and protein expression. The association between CD70 and patients' overall survival and its impact on T-cell death was also evaluated. Human and mouse CD70-specific chimeric antigen receptors (CARs) were tested respectively against human primary GBMs and murine glioma lines. The antitumor efficacies of these CARs were also examined in orthotopic xenograft and syngeneic models. Results: CD70 was not detected in peripheral and brain normal tissues but was constitutively overexpressed by isocitrate dehydrogenase (IDH) wild-type primary LGGs and GBMs in the mesenchymal subgroup and recurrent tumors. CD70 was also associated with poor survival in these subgroups, which may link to its direct involvement in glioma chemokine productions and selective induction of CD8+ T-cell death. To explore the potential for therapeutic targeting of this newly identified immunosuppressive axis in GBM tumors, we demonstrate that both human and mouse CD70-specific CAR T cells recognize primary CD70+ GBM tumors in vitro and mediate the regression of established GBM in xenograft and syngeneic models without illicit effect. Conclusion: These studies identify a previously uncharacterized and ubiquitously expressed immunosuppressive ligand CD70 in GBMs that also holds potential for serving as a novel CAR target for cancer immunotherapy in gliomas.